CRITERIA FOR THE SELECTION OF ANTIBIOTIC THERAPY IN RECONSTRUCTIVE AND RESTORATIVE ABDOMINAL SURGERY - Zebo Norbobaevna Sherova; Mohirjon Otabekovich Ekubzhanov (The Conference Hub, 2025)
According to the Surviving Sepsis Campaign (SSC) recommendations, ABP should be administered within 1 hour of admission to the ICU or emergency department.